Application of sports science to improve performance in the Australian Olympic skeleton program - Bullock, N.; Martin, D. T.; Gulbin, J.; Ross, A.; Marino, F. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
Introduction Millions of dollars are invested annually by countries around the world to achieve success at the Olympic Games. This monetary investment has been coupled with the growth of a relatively new industry - sports science. Many countries now employ teams of sport scientists in an attempt to improve international competitiveness with a focus on integrating science with coaching to obtain a result at the Olympic Games. Since skeleton was only reintroduced into the 2002 Winter Olympic Games it is still in its infancy with regards to sports science. Because of the lack of scientific literature, this research was based on a straightforward approach of identifying key performance variables in this sport. Studies Study 1 Official race times from World Cups over 4 years were analysed with linear mixed models. Within-athlete runto- run (between run) variability on the different tracks ranged from 0.19% to 0.56% for top-ranked men and 0.27% to 0.89% for top-ranked while race-to-race variability was 0.35% for men and 0.47% for women. The differences in run-to-run variability paralleled differences in popular opinion of technical difficulty of the tracks. There was an inconsistent and overall small relationship between push time and performance time on different tracks (range of correlations, 0.57 to -0.14; mean, 0.21). The home advantages of 0.15% for men and 0.32% for women were respectively trivial and substantial in relation to the smallest important performance changes of 0.18% and 0.23%, derived from race-to-race variability. Predictability of individual performance expressed as race-to-race correlations was modest (0.36 for males and females). Study 2 In many sports, changes in performance time between races arising from differences in venues and weather far exceed changes in an athlete`s true ability. Quadratic trajectories were fitted to each athlete`s race placing and to percent behind the winning time. A more sophisticated method fitted similar quadratic trajectories to race time using a mixed model to adjust for mean race times. Correlations between predicted and observed performance in the Olympics clearly favoured race placing (0.78) over race time (0.65) and percent behind the winner (0.63) for women, whereas race placing was clearly inferior (0.14) to percent behind the winner (0.30) and race time (0.46) for men. Study 3 Acceleration, capacity and load was quantified in the skeleton start at World Cup events. Velocity at 15-m accounted for ~86% of the variance in overall start time. Rapid acceleration to attain a high velocity at 15-m is the most important component of a fast overall start time of the variables analyzed in this study. The importance of the time to load and velocity at 45-m vary according to the different track characteristics. Study 4 A talent transfer model was used to rapidly develop and qualify an Australian female athlete in the skeleton event at the 2006 Torino Winter Olympic Games. The athlete who eventually represented Australia at the Torino Winter Olympic Games did so following ~300 start simulations and ~220 training/competition runs over a period of 14 months. Study 5 Whole body vibration was used as an ergogenic aid to enhance upright 30-m sprinting and explosive jumping (WBV; 30 Hz 3 x 1 min with a 1:3 work to rest ratio). 30-m upright sprinting declined in following WBV or CON treatment (0.7% decrement; p=0.03 v 1.4% decrement; p=0.05 respectively. Study 6 Using a higher WBV frequency (WBV; 45 Hz 3 x 1 min treatments separated by 1 min) maximal 30-m upright sprinting and bent over, skeleton push performance were examined before and 10 min after an acute bout of WBV or no vibration. All changes pre and post WBV were small or trivial and within the tests typical variation (~3.7% for the skeleton push and ~3.2% for the upright sprinting). Study 7 We looked at the effect of international travel on plasma and salivary cortisol levels in skeleton athletes. Saliva cortisol tended to be ~4% of plasma cortisol at baseline but decreased to ~2% on Day-2 and ~3.5% on Day-2 and Day-4. The relationship between salivary and plasma cortisol can change following international travel and the extent of the disturbance in cortisol concentrations after crossing multiple time zones may differ between plasma and saliva samples. Study 8 Athletes undertook long-haul eastward flight from Australia to Canada. Compared to baseline, average resting salivary cortisol decreased 67 % immediately following travel (23.43 ± 5.71 nM; p=0.03). No significant differences in 30-m sprint time between baseline and post-flight tests were found. Athletes perceived themselves as `jet-lagged` for up to two days post-flight (p=0.01). Despite a distinct phase-change in salivary cortisol rhythmicity and the athletes perceiving themselves as"jet-lagged" we observed minimal disturbances in `one-off` daily maximal sprinting ability after long-haul eastward travel. Conclusion: In less than 14 months Australia sent a novice Skeleton Athlete to the Winter Olympic Games, achieved two top-6 World Cup results and had an under-23 World Champion. The talent transfer model using deliberate programming provides a guide to the minimum exposure required for an Australian novice skeleton athlete to reach Olympic representative standard following 14 months of intensified sports specific training. Skeleton athletes show lower race-to-race variability in performance time than athletes in other sports, but race outcomes are largely unpredictable. More work is needed to increase our ability to track and predict performance of individual skeleton athletes. The difficulty of tracks varies substantially but is remarkably consistent from year to year. The contribution of the push phase to overall performance varies between tracks and gender. Regardless of track, 15-m velocity is the most important aspect of the push phase. To enhance athletes sprinting and skeleton push performance using realistic competition time frames the application of WBV was not convincing. Maximal sprinting ability was not significantly impaired by eastward long-haul travel when full-warm-up procedures were followed in athletes who displayed circadian disrhythmia. These results gave us confidence that skeleton start performance would not be impaired by long-haul jet travel.